The Influence of Business Model Innovation on Increasing Company Competitiviness in the Digital Era - Kardana, Heru dwi; Luwiha, Luwiha; Suryanadi, Juni; Majeed, Muhammad Kashif (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2025)
This study aims to investigate the impact of business model innovation on enhancing company competitiveness in the context of the digital era. As companies increasingly face challenges from rapid technological advancements and evolving consumer preferences, the need for strategic innovation becomes paramount. Business model innovation defined as the process of redesigning a company's core logic for creating and capturing value has been recognized as a key lever for maintaining relevance and achieving competitive advantage. Employing a descriptive quantitative research design, this study collected primary data through structured questionnaires administered to 90 respondents who are customers of the SRC Fitri store. Simple linear regression analysis was conducted to examine the relationship between business model innovation (independent variable) and company competitiveness (dependent variable). The analysis revealed that business model innovation has a statistically significant impact on competitiveness, accounting for 51.4% of the observed variance. The remaining 48.6% is attributed to other external factors not examined within this study. These findings underscore the strategic importance of business model innovation as a central factor in navigating digital disruption and market volatility. Companies that are able to rapidly innovate their business models in response to technological change and shifting customer demands are more likely to sustain long-term competitive advantage. This study contributes to the growing body of literature on strategic innovation and offers practical insights for business leaders seeking to strengthen their firm's adaptive capacity and competitiveness in the digital age.